Education of medical caregivers in Poland: areas requiring improvement – mixed-method research - Magdalena Krysińska-Pisarek; Katarzyna Domosławska-Żylińska; Piotr Tyszko (BMC Health Services Research)
Abstract Background Demographic changes associated with an ageing population, combined with the shortage of nursing personnel in Poland, have led to the introduction of a distinct new medical profession—the medical caregiver—which is separate from the nursing profession and has been officially included in the national classification of professions and specialties. In light of the demands of this role, a study was conducted with the primary objective of analysing educational outcomes and identifying areas requiring improvement in both theoretical knowledge and practical skills within the educational process for medical caregivers. Methods Convergent parallel mixed-methods design was used, with quantitative (Computer-Assisted Web Interview, CAWI and paper questionnaire)and qualitative components (3 mini Focus Group Interview, FGI) conducted concurrently and results integrated. Coding disagreements were resolved through discussion among the three researchers until consensus was reached. A total of 840 surveys were included in the analysis. Statistical analyses were conducted using the IBM SPSS Statistics 26.0 statistical package, STATISTICA version 12.0, and Excel spreadsheet software. Results Key areas of education identified as needing further development included: the fundamentals of care for ill and dependent individuals, essential aspects of medical care, personal and social competencies, health and safety at work, planning and performing hygiene and care activities for ill and dependent individuals and performing selected tasks tailored to the needs of individuals with dementia. Both survey respondents and FGI participants consistently identified insufficient training in practical skills and soft skills. Conclusions Our results explicitly identify specific training gaps in sign language, practical clinical skills, and stress management, supporting our recommendations for targeted improvements in these areas. Implementing these curriculum improvements would require coordinated efforts between educational institutions and healthcare employers.